2022
DOI: 10.1039/d1cp04448f
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization or bridging: which occurs faster is the key to the self-assembly mechanism of Pd6L3 coordination prisms

Abstract: The self-assembly processes of Pd6L3 coordination prisms consisting of cis-protected Pd(II) complexes and porphyrin-based tetratopic ligands with four 3-pyridyl or 4-pyridyl groups (L) were investigated by experimental and numerical methods,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
3
1
Order By: Relevance
“…Although the NASAP study is possible and actually being underway for larger self-assembly systems, coordination self-assembly systems with 6 metal ions are the largest ones reported in the publication. The system introduced here is another example from that group 102 From this study, contrary to common intuition, it was found that for both 8 and 9 macrocyclization (c) takes faster than bridging reaction (b), with the ordering being c-b-b-b after oligomerization. Bridging reaction prior to macrocyclization tended to lead to kinetically trapped species, and the relative magnitude of the rate constants between those two kinds of intramolecular reactions was found to be the key factor.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…Although the NASAP study is possible and actually being underway for larger self-assembly systems, coordination self-assembly systems with 6 metal ions are the largest ones reported in the publication. The system introduced here is another example from that group 102 From this study, contrary to common intuition, it was found that for both 8 and 9 macrocyclization (c) takes faster than bridging reaction (b), with the ordering being c-b-b-b after oligomerization. Bridging reaction prior to macrocyclization tended to lead to kinetically trapped species, and the relative magnitude of the rate constants between those two kinds of intramolecular reactions was found to be the key factor.…”
contrasting
confidence: 62%
“…Although the NASAP study is possible and actually being underway for larger self-assembly systems, coordination self-assembly systems with 6 metal ions are the largest ones reported in the publication. The system introduced here is another example from that group 102 (Fig. 2(f)), though the reaction network is smaller than the double-walled triangle (DWT) due to the metal ion having the coordination number of N = 2.…”
Section: Qasap-nasap Approachmentioning
confidence: 99%
“…2 The self-assembly of the [Pd614] 12+ TT was carried out by mixing cis-protected Pd(II) complex [PdPy*2] 2+ (Pd: Pd(TMEDA), Py*: 3chloropyridine) and tritopic ligand 1. 61 The time-course of the substrates ([PdPy*2] 2+ and 1) and the products ([Pd614] 12+ and Py*) were monitored by 1 H NMR spectroscopy and the information about the intermediates derived from average composition of all intermediates, n-k values, were also obtained by QASAP (quantitative analysis of self-assembly process [52][53][54][55][56][57][60][61][62][63] ) (Fig. 4a and b).…”
Section: Pathway Selection In Molecular Self-assembly Of Pd6l4 Cagementioning
confidence: 99%
“…4a and b). The species in the self-assembly can be generally expressed as The experimental data thus obtained were numerically analyzed by NASAP (numerical analysis of self-assembly process) [58][59][60][61][62][63] . A reaction network model shown in Fig.…”
Section: Pathway Selection In Molecular Self-assembly Of Pd6l4 Cagementioning
confidence: 99%